Control of the nuclear localization of Extradenticle by competing nuclear import and export signals - Abu-Shaar, Muna (Cold Spring Harbor Laboratory Press, 1999)
The Drosophila PBC protein Extradenticle (Exd) is regulated at the level of its subcellular distribution: It is cytoplasmic in the absence of Homothorax (Hth), a Meis family member, and nuclear in the presence of Hth. Here we present evidence that, in the absence of Hth, Exd is exported from nuclei due to the activity of a nuclear export signal (NES). The activity of this NES is inhibited by the antibiotic Leptomycin B, suggesting that Exd is exported by a CRM1/exportin1-related export pathway. By analyzing the subcellular localization of Exd deletion mutants in imaginal discs and cultured cells, we identified three elements in Exd, a putative NES, a nuclear localization sequence (NLS), and a region required for Hth-mediated nuclear localization. This latter region coincides with a domain in Exd that binds Hth protein in vitro. When Exd is uncomplexed with Hth, the NES dominates over the NLS. When Exd is expressed together with Hth, or when the NES is deleted, Exd is nuclear. Thus, Hth is required to overcome the influence of the NES, possibly by inducing a conformational change in Exd. Finally, we provide evidence that Hth and Exd normally interact in the cytoplasm, and that Hth also has an NLS. We propose that in Exd there exists a balance between the activities of an NES and an NLS, and that Hth alters this balance in favor of the NLS.